Small-Sized Parabolic Trough Collector System for Solar Dehumidification Application: Design, Development, and Potential Assessment - Ghulam Qadar Chaudhary; Rubeena Kousar; Muzaffar Ali; Muhammad Amar; Khuram Pervez Amber; Shabaz Khan Lodhi; Muhammad Rameez ud Din; Allah Ditta (International Journal of Photoenergy)
The current study presents a numerical and real-time performance analysis of a parabolic trough collector (PTC) system designed for solar air-conditioning applications. Initially, a thermodynamic model of PTC is developed using engineering equation solver (EES) having a capacity of around 3 kW. Then, an experimental PTC system setup is established with a concentration ratio of 9.93 using evacuated tube receivers. The experimental study is conducted under the climate of Taxila, Pakistan in accordance with ASHRAE 93-1986 standard. Furthermore, PTC system is integrated with a solid desiccant dehumidifier (SDD) to study the effect of various operating parameters such as direct solar radiation and inlet fluid temperature and its impact on dehumidification share. The experimental maximum temperature gain is around 5.2°C, with the peak efficiency of 62% on a sunny day. Similarly, maximum thermal energy gain on sunny and cloudy days is 3.07 kW and 2.33 kW, respectively. Afterwards, same comprehensive EES model of PTC with some modifications is used for annual transient analysis in TRNSYS for five different climates of Pakistan. Quetta revealed peak solar insolation of 656 W/m2 and peak thermal energy 1139 MJ with 46% efficiency. The comparison shows good agreement between simulated and experimental results with root mean square error of around 9%.